Człowiek bez ojczyzny – powtórzona lektura „Listu o humanizmie” Heideggera - Kołoczek, Łukasz (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The article is an attempt to read the Letter of humanismin the light of the project Beyng. First of all I say that the figure of Da-sein is crucial for understanding the Letter. My considerations focus in particular on the position which a man occupies in the structure of Da-sein. I show that there is an analogy between this structure and the considerations of the Letter. I say also that this letter made transposition of the term „humanism” into the other beginning. The project of humanism, which emerges from this text does not coincide neither with today’s varieties of humanism, nor the post-humanism, because both of these forms of thought are inscribed in metaphysics. In this context „no homeland” of which Heidegger says in the Letter, takes on special significance, which I wanted to show.